Ladder-simulation elliptic bandpass active-RC filter structure employing identical resistors - Mahattanakul, J.; Khumsat, P.; Surakampontorn, W. (My University, 2009)
A novel structure of the ladder-based elliptic bandpass active-RC filter is presented. Unlike the previously reported elliptic bandpass active-RC filter, the proposed filter contains resistors with identical value and is therefore more suitable for integrated-circuit realisation. Also, according to the simulation results, the proposed elliptic bandpass filter performs better than the reciprocator-based active-RC filter, which employs identical resistors, in terms of noise, power and area. Additionally, the proposed filter structure was also found to be less sensitive than both of the aforementioned structures. © The Institution of Engineering and Technology 2009.